Conocimiento y aplicación de técnicas de higiene íntima femenina en usuarias del Subcentro Santa Clara, Pastaza. Año 2015 - Guevara Triviño, Lizbeth Jacqueline (2016)
This study determined the level of awareness and feminine hygiene practices that women who visit Subcentro de Salud Santa Clara de Pastaza have. The research design used was cross-sectional, descriptive, exploratory, bibliographical and included fieldwork. Surveys were conducted in 60 women for data collection purposes. According to the results, female patients who often visit the Centre are aged 20-39, which accounts for 55%. 60% of them are mestizo while 40% are indigenous. 51,67 % have finished primary school and 40% have done high school. They claim agriculture and livestock farming are their source of employment in a 36.67%. As for knowledge of feminine hygiene, it was found that 85 % do not know its benefits, 81.67 % do not know the consequences and 80% are not aware of the diseases that can be contracted due to an incorrect cleaning of the genital area; therefore, their general knowledge about intimate feminine hygiene techniques is low: 91.67 %. Regarding the use of proper personal hygiene techniques, only 33.33 % of them performed them front to back, 32% wash themselves twice a day, 31.67 % use soap, and 20% wear cotton underwear, which means their level of implementation of personal hygiene techniques is low: 65%. The main causes for the failure to apply the techniques of personal hygiene are ignorance and neglect at 100 %, followed by a 96.67 % corresponding to incorrect habits, and lack of water at 95%. In conclusion, very few women are aware of the importance of feminine hygiene practices. Consequently, a plan of intervention based on educational activities and training workshops has been developed